Permeability properties of self-compacting concrete with coarse recycled aggregates - Oliveira, Luiz Antonio Pereira de (2014)
This article addresses to the issue of durability related properties of self-compacting concrete (SCC) with the use of coarse recycled aggregates obtained from demolition of concrete structures. The objective was to verify the influence of recycled aggregates on SCC permeability properties. For this purpose four different types of concrete mixes were produced, one of them used as reference with natural coarse aggregates and the others prepared with 20%, 40% and 100% of recycled coarse aggregates. The properties related to the durability of SCC, as air and water permeability and capillary absorption were determined on concrete specimens with and without preconditioning. The results from fresh and hardened concrete properties lead to the conclusion that it is viable to replace natural coarse aggregates by recycled coarse aggregates since the present research does not show any detrimental to the SCC permeability properties.